ANALYSIS POTENTIAL AND CONTRIBUTION OF HOTEL TAX TO THE REGIONAL INCOME (PAD) IN BENGKALIS REGENCY (A CASE IN BENGKALIS REGENCY) - Wahyuni, Sri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research has the purpose to know how large is the potential and contribution of hotel tax to the Regional Income (PAD) in Bengkalis Regency. Type of research that used in this research is quantitative descriptive. The method that used in collecting data are library study, documentation, interview, and observation. The results of this research conclude that potential of hotel tax in Bengkalis Regency is very high, but not all potential can be realized. It can be seen with different calculate between potential and realization revenue of hotel tax 66.74% in 2009, 73.25% in 2010, and 75.67% in 2011. In other words, the realization of hotel tax that was achieved within the three consecutives years, 33.26% in 2009, 26.75% in year 2010, and 24.33% in year 2011Â from the real potential revenue of hotel tax. Otherwise, the contribution of hotel tax to Regional Income (PAD) inclined decrease. Â Key Words: Potential, Contribution, Realization, Hotel Tax